2012
DOI: 10.1371/journal.ppat.1002927
|View full text |Cite
|
Sign up to set email alerts
|

Kaposi's Sarcoma Herpesvirus K15 Protein Contributes to Virus-Induced Angiogenesis by Recruiting PLCγ1 and Activating NFAT1-dependent RCAN1 Expression

Abstract: Kaposi's Sarcoma (KS), caused by Kaposi's Sarcoma Herpesvirus (KSHV), is a highly vascularised angiogenic tumor of endothelial cells, characterized by latently KSHV-infected spindle cells and a pronounced inflammatory infiltrate. Several KSHV proteins, including LANA-1 (ORF73), vCyclin (ORF72), vGPCR (ORF74), vIL6 (ORF-K2), vCCL-1 (ORF-K6), vCCL-2 (ORF-K4) and K1 have been shown to exert effects that can lead to the proliferation and atypical differentiation of endothelial cells and/or the secretion of cytokin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

8
92
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 51 publications
(101 citation statements)
references
References 54 publications
(140 reference statements)
8
92
1
Order By: Relevance
“…The K15 Y 481 F mutant was impaired in the induction of NF-B/DNA complex formation (Fig. 1C), which, in addition to previously reported experiments (16)(17)(18), provides further evidence for the importance of the Y 481 EEV motif for K15-mediated downstream signaling.…”
Section: Discussionsupporting
confidence: 83%
See 4 more Smart Citations
“…The K15 Y 481 F mutant was impaired in the induction of NF-B/DNA complex formation (Fig. 1C), which, in addition to previously reported experiments (16)(17)(18), provides further evidence for the importance of the Y 481 EEV motif for K15-mediated downstream signaling.…”
Section: Discussionsupporting
confidence: 83%
“…Previous studies showed that the K15 protein of KSHV induces several signal transduction pathways, including the activation of NF-B (16)(17)(18). Induction of NF-B via the classical or the alternative pathway is accompanied by the translocation of specific NF-B dimers from the cytoplasm to the nucleus.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations